Evaluasi Implementasi Kurikulum Perpajakan dengan Model CIPP pada Program Keahlian Akuntansi dan Keuangan Lembaga: Studi Multisitus pada Tiga SMK di Jakarta: (Evaluation of Taxation Curriculum Implementation Using the CIPP Model in Accounting and Institutional Finance Programs: A Multi-Site Study at Three Vocational High Schools in Jakarta) - Guntur Ilhamsyah; Yulianto; Indriani Rahayu NingTyas (Institut Ilmu Sosial dan Manajemen STIAMI, 2026)
requires vocational high school graduates to possess taxation competencies that align with the needs of business and industry. However, the taxation curriculum implemented in Accounting programs at vocational High Schools (SMKs) remains largely focused on Income Tax Article 21 and does not adequately reflect the broader competencies required in taxation practice. This study aims to evaluate the tacation curriculum policy in accounting programs at Cocational High Schools In Supporting the development of taxation human resources. A qualitative approach was employed using a case study of SMK Binawarman, SMK PGRI 15 Jakarta, and SMK PGRI 37 Jakarta through curriculum document analysis, interviews, and observations. The findings reveal that witholding ang collection tax materials, Including Income Tax Articles 22, 23, and 26. as well as value added tac (VAT). Are not cufficiently covered in the curriculum. As a result, the tacation of the labor market, ehich demands a broader understanding of taxation regulations and administrative practices. The study concludes that the current taxation curriculum has not adequately supported graduates job readiness in the fields of accounting and taxation. Therefore, cuttuculum development is needed to provide more comprehensive taxatio comptencies that are aligned with the needs of business and industry